Pelatihan Desain Kreatif Canva dalam Sosial Media di Lingkup Kelurahan Se-Kecamatan Pangkajene - Elfira Makmur; Sari, Dessy Ana; Hilda Ashari; Muh. Iswal Burhan; Akhyar Muchtar (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
The creativity training program in sub-district units of Pangkajene District is an effort to strengthen the competency of government personnel in accelerating delivery of attractive and technology-based information. Social media is an important component of any instances to raise consumer’s awareness. It is hoped that by offering useful and attractive digital contents, sub-district units of Pangkajene District will be able to minimize the spread of fake news and many other useful information for citizen. With this program, our teams demonstrated various materials and cases using Canva application to generate an attractive and informative digital content, specifically by utilize Canva’s features and template.